A novel simplified model for torsional vibration analysis of a series-parallel hybrid electric vehicle. (15th February 2017) - Tang, Xiaolin; Yang, Wei; Hu, Xiaosong; Zhang, Dejiu
Abstract: In this study, based on our previous work, a novel simplified torsional vibration dynamic model is established to study the torsional vibration characteristics of a compound planetary hybrid propulsion system. The main frequencies of the hybrid driveline are determined. In contrast to vibration characteristics of the previous 16-degree of freedom model, the simplified model can be used to accurately describe the low-frequency vibration property of this hybrid powertrain. This study provides a basis for further vibration control of the hybrid powertrain during the process of engine start/stop. Highlights: A novel simplified torsional vibration dynamic model is established. Comparison with the full-order model is made. The accuracy of the simplified model is verified. Guiding vibration control of hybrid powertrain during frequent engine start/stop.